Translation Techniques of Medical Terms Found in Covid-19 Guidebook - Ismi Ovianti Restiana; Raden Arief Nugroho (Journal of English Language Teaching and Linguistics, 2021)
This study was conducted to find and analyze the use of translation techniques used by translators in translating various medical terms contained in the COVID-19 guidebook based on the theory from Rask (2008). The categories of medical terms used in this study are medical terms, epidemiological terms, and organizational terms. This study uses the descriptive qualitative method. The data were obtained through classifying and describing the medical terms in the COVID-19 guidebook according to the types of translation techniques based on Molina & Albir (2002). The findings show the type of translation technique, that has been found in this study, which gets a percentage of 63,54% as the highest frequency reaching 739 is Established Equivalence in all categories. Interestingly, it can be seen that translators are very concerned about the use of grammatical structures in the source language. Since the grammatical structure in the source language is different from the target language, translators also tend to use a more common language taken from the dictionary but equivalent to the target language.